First records of several bird species for Zacatecas, Mexico - Alejandro Pérez-Arteaga; Silvia S. Zalapa; Sergio Guerrero; Daniel Cruz-Sáenz (Huitzil, 2017)
We report the first records of five species of birds for the state of Zacatecas, Mexico: Ortalis poliocephala (West Mexican Chachalaca), Progne sinaloae (Sinaloa Martin), Peucaea carpalis (Rufous-winged Sparrow), Melospiza melodia (Song Sparrow) and Cyanocompsa parellina (Blue Bunting). Ortalis poliocephala is also a new record for the Western Sierra Madre biogeographic region. These records are ecologically relevant as they extend the known distribution ranges and suggest that the southern Zacatecas region might be more diverse than previously thought.